The effect of quench cracks and retained austenite on the hydrogen trapping capacity of high carbon martensitic steels. (26th April 2021) - Pinson, M.; Springer, H.; Depover, T.; Verbeken, K.
Abstract: Hypereutectoid martensitic steels possess excellent hardness levels which make them attractive materials for specific industrial applications. However, they can contain cracks and/or retained austenite after quenching which show a particular interaction with hydrogen (H). Hence, this work evaluates the interaction between H and a martensitic Fe-1.1C alloy by combining a wide variety of (H) characterization techniques with a systematic approach for specially designed H charged and heat treated samples. A detailed analysis of the microstructure for every condition serves as the basis for the interpretation. The results show that the presence of H leads to additional cracking and branching or growth of pre-existing quench cracks. Moreover, it is shown that when the temperature exceeds the retained austenite decomposition temperature while the austenitic grains contain H, additional cracking occurs which increases the amount of reversible H trapping sites thus raising the HE susceptibility. Graphical abstract: Image 1 Highlights: Strong interaction between hydrogen and quench cracks/retained austenite. Hydrogen causes crack initiation and propagation in hypereutectoid steels. Quench cracks and hydrogen induced cracks increase weak H trapping sites. Retained austenite acts as a strong trapping site. Presence of hydrogen in retained austenite is harmful at elevated temperature.